Mean stress sensitivity and crack initiation mechanisms of spring steel for torsional and axial VHCF loading. (December 2016) - Mayer, Herwig; Schuller, Reinhard; Karr, Ulrike; Fitzka, Michael; Irrasch, Daniel; Hahn, Malte; Bacher-Höchst, Manfred
Highlights: Pronounced mean stress sensitivity of VHCF torsional and axial strength is found. Cracks in cyclic torsion mostly initiate by cyclic shear without a crack starter. Cracks in cyclic tension mostly start at internal inclusions or grain boundaries. Initial shear cracks deflect to mode I at a well-defined stress intensity factor. Residual stresses are stable under axial but not under torsional VHCF loading. Abstract: The very high cycle fatigue (VHCF) properties of shot-peened VDSiCr spring steel have been investigated with the ultrasonic fatigue testing method. Fatigue behaviour under cyclic torsion and cyclic tension loading at load ratios between R = −1 and R = 0.5 is compared. For 90% of the VHCF failures under axial loading, fractured grain boundaries or inclusions in the interior of the material act as crack starters. In contrast, the initial crack is produced by cyclic shear in the interior or, less frequently, at the surface for more than 90% of the VHCF failures under torsional loading. The crack path deflects from mode II/mode III to mode I at the border of the initiating shear area. The change of crack path correlates to a stress intensity factor range for a crack loaded in shear mode of Δ K τ, ISA = 5.6 ± 0.5 MPam 1/2 for load ratio R = 0.1 and Δ K τ, ISA = 3.8 ± 0.4 MPam 1/2 for R = 0.35, respectively. Residual stresses due to shot-peening are stable during VHCF axial loading while they are reduced during VHCF torsional loading.